PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 61 HARAPAN BARU - ', Ngatminten; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of Contextual Teaching Leraning IPA class IV SD Negeri 61 Harapan Baru from 22 student who achieve KKM just 5 student (22,72%) while students who did’nt complete 17 students (77,28%) with an average of 56,77 . The purpose of this research to improve Contextual Teaching Leraning IPA class IV SD Negeri 61 Harapan Baru with the application of learning models Contextual Teaching Leraning. The result obtained by the average value of 56,77 basic score increased in the first cycle of 25,13% to 71,04 . In the second cycle the average value of student also increased by 42,34 % to 80,81 . On the basis of completeness score IPA student learning outcomes is only56,77 (not finished). After the professor of applied learning Contextual Teaching Leraning in the first cycle classical completeness increased to 22,72% (not finished), the second cycle of classical completeness obtained are increased to increase to 90,90% . Activities of teachers at the first meeting of 62,5% with both categories. The second meeting increased to 68,75% in both categories. In the second cycle increased to 87,5% with the category very well. At a meeting of the second meeting of the second cycle, the activities of the teachers increased to 93,75% with the category very well. Activites of students in the first cycle of the first meeting actifity students acquire a percentage of 62,5% in both categories . The second meeting of the first cycle to 68,75% in both categories . At the first meeting of the second cycle of student actifity increased to 81,25% with the category very well, and at the second meeting of the second cycle increased again to 87,5% with the category very well. Key Words : Contextual Teaching and Leraning, learning outcomes IPA